Pengaruh Pengelolaan Aset Tetap dan Belanja Modal terhadap Efektivitas Pemanfaatan Aset di Dinas Kesehatan Kota Kupang (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to determine the effect of fixed asset management and capital expenditure on the effectiveness of asset utilization at the Kupang City Health Office. This research employs a field study method with a quantitative approach. The population of this study consists of all employees in the work units of the Kupang City Health Office. Using the purposive sampling method, a total of 54 respondents were selected, consisting of those working in the finance division, asset management, analysis, and planning. The data used are primary data collected through questionnaires. The data were processed using SPSS version 27. The data analysis techniques applied include data instrument testing, descriptive statistical analysis, multiple linear regression analysis, and classical assumption testing. The results of the study show that, partially, fixed asset management has no significant effect on the effectiveness of asset utilization, while capital expenditure has a significant effect on the effectiveness of asset utilization. Furthermore, simultaneously, fixed asset management and capital expenditure have a significant effect on the effectiveness of asset utilization at the Kupang City Health Office.